Circuit Modeling of the Impact of Heavy Charged Particles on Transient Processes in Bipolar Analog Microcircuits - O. V. Dvornikov; V. A. Tchekhovski; I. Yu. Lovshenko; Trong Thanh Nguyen (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
One of the factors causing the failure of spacecraft integrated circuits is exposure to heavy charged particles. The entry of heavy charged particles into electronic devices leads to the appearance of single event transients (short current pulses), which in analog microcircuits manifest themselves in distortion of the output signal shape, and in digital microcircuits can cause a single event upset. The article discusses a technique for circuit mode-ling of the eﬀect of heavy charged particles on bipolar analog microcircuits, including the developed equivalent electrical circuit of a bipolar transistor for LTSpice and the procedure for modeling transient processes. Despite the simpliﬁcations adopted, namely: failure to take into account the dependence of the duration of the rise and fall of the current pulse generated by a charged particle on the parameters of the transistor structure, the assumption that the entire charge is generated in the active base and the space charge regions of the emitter and collector junctions, an equivalent circuit has been developed made it possible to determine that the shape of the collector current pulse for circuit with a common emitter when exposed to a heavy charged particle is determined by the speed of the transistor and its operating mode. Using the developed methodology, the “critical” transistors of the two studied analog microcircuits were determined, and the need to bypass the current-setting resistors with a small capacitor was justiﬁed.